On the performance of uplink D2D-assisted backscatter employing short packet communication - Si-Phu Le; Bui Vu Minh; Vu Quang Sy; Miroslav Voznak (PLoS ONE, 2025)
This paper examines the synergistic integration of uplink Device-to-Device (D2D), backscatter, and short-packet communication paradigms, highlighting their collective potential to revolutionize next-generation wireless systems. By enhancing spectral efficiency and supporting massive connectivity through diverse receiver techniques, this approach is undeniably transformative. Then, we analyze the approximation forms of average block error ratio (BLER) across three scenarios: selective combining - random selection (SC-RAN), selective combining - maximal ratio combining (SC-MRC), and full-maximal ratio combining (Full-MRC). Results indicate that the full-MRC scheme consistently outperforms the others in reducing BLER, particularly in low-latency scenarios. The findings serve as a foundation for making strategic design decisions about the system’s core operational parameters. Our numerical results strongly validate our analytical findings, clearly demonstrating that the full-MRC technique significantly outperforms others in improving BLER.